Tracking changes in the occurrence and source of pharmaceuticals within the River Thames, UK; from source to sea. (June 2019) - White, Debbie; Lapworth, Dan J.; Civil, Wayne; Williams, Peter
Abstract: There is a growing interest in the occurrence and sources of pharmaceutical substances in the environment. This paper reports the first detailed transect of pharmaceutical occurrence along the River Thames, UK, from source to sea, undertaken during a period of high flow in 2016. In 37 samples a total of 41 pharmaceuticals and 2 lifestyle compounds (cocaine and sucralose) were detected. Total concentration of pharmaceuticals ranged from 0.0012 μg/l to 10.24 μg/l with a median of 2.6 μg/l. Sucralose concentrations varied from <0.01 to 5.9 μg/l with a median concentration of 1.93 μg/l and was detected in every sample except the groundwater-dominated sources of the Thames. Antimicrobials, including those on the surface water watch list (erythromycin, clarithromycin and azithromycin) were detected in every site downstream of the Thames source. Diclofenac, recently on the surface water watch list, was detected in 97% of Thames samples and above the proposed EQS of 0.1 μg/l in 12 samples. Distinct increases in concentration and number of pharmaceuticals were found downstream of the Oxford, Mogdon and Hogsmill wastewater treatment works (WWTW) but were more subdued downstream of the Crossness and Beckton WWTW due to the tidal nature of the Thames and combined sewer outflows. Sucralose was found to be an excellent tracer of wastewaters (treated and untreated) and can be used as a proxy for many pharmaceuticals. Paracetamol and ibuprofen were tracers of untreated wastewater inputs to the Thames due to their high biodegradation within WWTWs. Graphical abstract: Image 1 Highlights: Pharmaceutical contamination is linked to WWTW discharge and untreated wastewater. Sucralose was found to be an excellent proxy for pharmaceutical contamination. Diclofenac was detected above a proposed EQS of 0.1 μg/l. Antimicrobials found in every site except the groundwater dominated Thames source.